Managing the ASEAN economic integration process in the Philippines an assessment of progress in trade liberalization and facilitation - Medalla, Erlinda M. (Philippine Journal of Development, 2012)
This paper is part of the Philippine study for the Mid-Term Review (MTR) of the ASEAN Economic Community (AEC) Blueprint, a project of the Economic Research Institute for ASEAN and East Asia (ERIA). A milestone in ASEAN economic cooperation is the Cebu Declaration on the Acceleration of the Establishment of an ASEAN Community by 2015 during the 12th ASEAN Summit in 2007, and subsequently the passing of the ASEAN Charter. A midterm review of where the member-countries are in moving toward the AEC is thus timely.